2018
DOI: 10.3174/ajnr.a5558
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT in Hemorrhagic Progression of Cerebral Contusion: Overestimation of Hematoma Volumes on Standard 120-kV Images and Rectification with Virtual High-Energy Monochromatic Images after Contrast-Enhanced Whole-Body Imaging

Abstract: The 120-kV images, which are comparable with single-energy CT images, significantly overestimated the hematoma volumes, hence the rate of hemorrhagic progression of contusions, after contrast-enhanced whole-body CT. Hence, follow-up of hemorrhagic contusions should be performed on dual-energy CT, and 190-keV images should be used for the assessment of hematoma volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…When it comes to different types of hemorrhage detection in patients with TBI, thin-section virtual high-energy monochromatic images at 190 keV created with DE CT were found to be superior to standard CT images in the detection of subdural hematomas, supratentorial contusions, and epidural hematomas, while subarachnoid bleeds were best depicted with standard 120-keV images (9). More directly related to the current work, the same team has shown that when follow-up of hemorrhagic contusions is performed with unenhanced CT after contrast material has been administered for polytrauma wholebody CT, virtual unenhanced images created with DE CT more accurately depicted contusion progression because conventional CT results in overestimation of hematoma volume secondary to contrast material leakage (10). While these prior studies have shown that DE CT can be useful to compensate for confounding contrast material leakage artifacts observed in patients undergoing a contrast-enhanced polytrauma whole-body CT protocol, the present work is important in its suggestion that contrast material administration and DE CT may actually be advantageous as a biomarker of secondary injury mechanisms driving HPC.…”
mentioning
confidence: 69%
“…When it comes to different types of hemorrhage detection in patients with TBI, thin-section virtual high-energy monochromatic images at 190 keV created with DE CT were found to be superior to standard CT images in the detection of subdural hematomas, supratentorial contusions, and epidural hematomas, while subarachnoid bleeds were best depicted with standard 120-keV images (9). More directly related to the current work, the same team has shown that when follow-up of hemorrhagic contusions is performed with unenhanced CT after contrast material has been administered for polytrauma wholebody CT, virtual unenhanced images created with DE CT more accurately depicted contusion progression because conventional CT results in overestimation of hematoma volume secondary to contrast material leakage (10). While these prior studies have shown that DE CT can be useful to compensate for confounding contrast material leakage artifacts observed in patients undergoing a contrast-enhanced polytrauma whole-body CT protocol, the present work is important in its suggestion that contrast material administration and DE CT may actually be advantageous as a biomarker of secondary injury mechanisms driving HPC.…”
mentioning
confidence: 69%
“…For measuring the iodine concentration in the contusion, DECT data from follow-up head CT studies were used with the modified Brain Hemorrhage application on the postprocessing workstation (syngo.via). 2 In patients with .1 follow-up head CT, measurements were also obtained from the second follow-up study to facilitate the calculation of the fractional rate of iodine washout from the contusions. Average iodine concentration was measured by drawing an ROI around each contusion.…”
Section: Image Analysis Of Dect and Definitionsmentioning
confidence: 99%
“…Pseudohematoma is defined as enhancing penumbra caused by an iodine leak on follow-up 120-kV images. 2 The attenuation contribution of iodine tends to be negligible at 190 keV, therefore demonstrating attenuation only from the hematoma, allowing measurement of true hematoma volume. 2 Hence, with the availability of hematoma volume on 120 kV-(true hematoma Ăľ enhancing penumbra) and true hematoma volume on 190-keV images, the pseudohematoma volume can be calculated as the following: Pseudohematoma Volume = (B -C), where B is the volume on 120-kV and C is volume on 190-keV images.…”
Section: Study Term Definitionsmentioning
confidence: 99%
See 2 more Smart Citations